Aktivitas Yoga Sebagai Produk Pemasaran Jasa Wisata Spiritual - Pradna Lagatama; Nyoman Danendra Putra (UHN IGB Sugriwa Denpasar, 2020)
Spiritual tourism is one of the attractions of tourism developed into a trend in the world of tourism which tends to continue to increase. Spiritual tourism is one of the destinations as a psychiatric recreation option that can be done by individuals or groups of people. Anyone both foreign and domestic tourists want to visit spiritual tourism as an alternative attraction and special interest. The potential of existing spiritual tourism is a natural tourist capital as a tourist attraction. The potential for existing spiritual tourism, is the capital in developing the tourism sector. Spiritual tourism objects need to be continuously built and developed in accordance with the wishes and expectations that can meet the needs of tourists so that tourists are moved to buy and use it if the products they market are in accordance with their needs. In the development of spiritual tourism there needs to be a breakthrough to attract more tourists who visit. One of them is by marketing yoga activities in the development of spiritual tourism. This marketing is done so that product producers can satisfy the wants and needs of consumers. With the marketing of yoga activities it is expected to be an added value for visitors so that they get what visitors need and want by introducing and offering yoga activities as one of the attractions of spiritual tourism.